Planning of Waste Management System in the Al-Amin Living Lab and Industrial Park Area, Sampecita Village, Kutalimbaru Sub-District - Rahmadhani Fitri; Faurantia Faurlana Sigit; Benny Iskandar; Andini Rahmadani (International Forum of Researchers and Lecturers, 2024)
The growth rate of the population has become a problem in the environmental context, both at the regional, national, and global levels. This issue has become a topic with the awareness that an increase in population affects human socio-economic activities that threaten the environment. This research aims to find out the waste management system planning in the Al-Amin Living Lab and Industrial Park area. This type of research is qualitative descriptive research with a literature study research method through a literature study derived from previous research journals related to the title. The results of this study indicate that the waste management planning in Kutalimbaru Sub-District, Sampe Cita Village, in the Al-Amin Living Lab and Industrial Park area focuses on the Indonesian National Standard (SNI) 3234-2008, including activities such as sorting, composting, and recycling. Implementing a new waste management paradigm, such as collecting, sorting, transporting, processing, and disposing, views waste as a resource with economic value that can be utilized.